Comparative cyclic voltammetry and SEM analysis of tin electrodes in citrate buffer solutions - Gervasi, Claudio (2007)
The anodic oxidation of tin in citrate buffer solutions has been studied by cyclic voltammetry and scanning electron microscopy. In order to identify each individual process, a numerical method was used to resolve into single processes the electrochemical behaviour.The results indicate that primary passivation is due to the formation of a Sn(II)-containing surface film. This film is not further oxidized at higher anodic potentials. There is evidence that during secondary passivation direct oxidation of Sn to Sn(IV) takes place, either as soluble ions or as a hydroxide layer. The results of this work improve, as well as, confirm theories previously advanced.